2018
DOI: 10.1080/15384101.2018.1542898
|View full text |Cite
|
Sign up to set email alerts
|

MAPT (Tau) expression is a biomarker for an increased rate of survival in pediatric neuroblastoma

Abstract: Although the impact of MAPT (Tau) expression has been well documented for neuronal cells in the context of tauopathies and neurodegenerative diseases, the impact and role of Tau expression in cancer, and specifically cancers of neuronal origin, is in its infancy. To determine the correlation between MAPT expression and survival in pediatric neuroblastoma, MAPT gene expression for samples from the TARGET pediatric neuroblastoma dataset was assessed. Initial analyses indicated that increased MAPT expression corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 36 publications
1
22
0
Order By: Relevance
“…Both genes are associated with neurodegenerative diseases, and in neuroblastoma, ectopic expression of ATXN2 sensitizes MYCN expressing cells to apoptosis [83]. Tau protein (MAPT) was not significant in any of our analyses, although one report found that Tau expression in neuroblastoma correlated with increased overall survival in neuroblastoma [84]. Tau is also a well-reported RBP in neurodegenerative diseases.…”
Section: Rbps Associated With Lower-risk Groupings and Involved In Nementioning
confidence: 58%
“…Both genes are associated with neurodegenerative diseases, and in neuroblastoma, ectopic expression of ATXN2 sensitizes MYCN expressing cells to apoptosis [83]. Tau protein (MAPT) was not significant in any of our analyses, although one report found that Tau expression in neuroblastoma correlated with increased overall survival in neuroblastoma [84]. Tau is also a well-reported RBP in neurodegenerative diseases.…”
Section: Rbps Associated With Lower-risk Groupings and Involved In Nementioning
confidence: 58%
“…Consistent with these data, in the TAU mRNA-top quintile group, transcriptional activity was higher for proapoptotic genes and lower for proliferation-associated genes. A similar analytical approach in pediatric neuroblastoma also revealed a better prognosis for the top quintile according to the MAPT transcript analyzed on microarray (NCBO BioPortal) [112]. Again, the data were substantiated with a significant correlation with apoptotic-and proliferation-linked genes.…”
Section: Tau and Cancermentioning
confidence: 79%
“…Again, the data were substantiated with a significant correlation with apoptotic-and proliferation-linked genes. In contrast, increased survival was not associated to the mRNA for alpha-synuclein, another neurodegeneration-associated protein [112]. Evidence that transcription alterations for genes associated with neurodegenerationwith the exception of MAPT -are not common drivers of gliomas was confirmed in another study, suggesting an important role of TAU in slowing down or preventing the clinical evolution of these tumors [113].…”
Section: Tau and Cancermentioning
confidence: 96%
“…MAPT is a gene encoding Tau protein, which is implicated in the pathogenesis of a number of neurodegenerative disorders, including Parkinson's disease, Alzheimer's disease, and progressive supranuclear palsy [26]. Recent studies have suggested that high MAPT expression predicts better survival outcomes in pediatric neuroblastoma, low-grade glioma, breast cancer and clear renal cell cancer [27][28][29]. Additionally, Wang et al reported that MAPT-hypermethylated tumors are associated with poor prognosis in patients with colorectal cancer [30].…”
Section: Discussionmentioning
confidence: 99%